Ontological aspects of quantum field theory - Kuhlmann, Meinard; Lyre, Holger; Wayne, Andrew (Singapore World Scientific, 2002)
This book is ideally suited to anyone with an interest in the foundations of quantum physics, including physicists, philosophers and historians of physics, as well as general readers interested in philosophy or science.
Includes bibliographical references and index.
Keywords: Cơ bản